The Role of Influencer Marketing, Customer Feedback, Corporate Social Responsibility, and Product Quality on Brand Image and Customer Loyalty in the Beauty and Personal Care Market in Indonesia - Rachmawati, Erny (Eastasouth Institute, 2024)
This study examines the effects of influencer marketing, customer feedback, corporate social responsibility (CSR), and product quality on brand image and customer loyalty in the beauty and personal care industry in Indonesia. A quantitative methodology was employed to collect data from a sample of 300 participants. The collected data was then analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The findings demonstrate substantial favorable impacts of influencer marketing, consumer feedback, corporate social responsibility (CSR), and product quality on brand image. Moreover, the brand image greatly amplifies client loyalty. The study illustrates that influencer marketing and corporate social responsibility (CSR) play a vital role in establishing a favorable brand image while maintaining a high standard of product quality continues to be a significant factor in how the brand is perceived. These elements collectively contribute to an increased level of consumer loyalty. The results offer practical insights for beauty and personal care companies, emphasizing the significance of well-planned influencer collaborations, proactive customer involvement, strong corporate social responsibility activities, and unwavering product quality in cultivating consumer loyalty and enhancing brand reputation.